2016
DOI: 10.17554/j.issn.2224-3992.2016.05.658
|View full text |Cite
|
Sign up to set email alerts
|

Short Chain Fatty Acids from Fermentation By Endophytic Bacteria in Aloe Vera Leaf Rind and Gel

Abstract: Aloe vera extracts have antimicrobial and anti-fungal activities, which may be able to treat minor skin infections. In spite of these antimicrobial activities, the inner leaf gel containing acemannan: non-digestible polysaccharide, leads to fermentation with endophytic bacteria and results in bacterial growth promotion, while no short chain fatty acids were detected in the ether extract of the fermentation broth with the rind. Butyric acid was identified by GC/MSD analysis from ether extract of the gel ferment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…group exhibited Aloe Vera gel shows positive effects on cognitive function and mood in healthy adults and promises, when take orally, in supporting neurologic health and function [5] . In an early our in vitro study, the fermentation production of hydrophobic butyric acid was confirmed by endophytic bacteria within Aloe Vera gel, supporting the possible incorporation of Aloe Vera gel as prebiotics aimed at improving gastrointestinal health [6] . The effects of naturally occurring butyrate-producing probiotic Clostridium butyricum CGMCC0313.1 (CB0313.1) were examined by Shang H. group, in limiting the development of high fat diet (HFD)-induced obesity.…”
Section: Possible Prophylaxes Of Aloe Vera Gel Ingestion To Butyrate mentioning
confidence: 61%
See 1 more Smart Citation
“…group exhibited Aloe Vera gel shows positive effects on cognitive function and mood in healthy adults and promises, when take orally, in supporting neurologic health and function [5] . In an early our in vitro study, the fermentation production of hydrophobic butyric acid was confirmed by endophytic bacteria within Aloe Vera gel, supporting the possible incorporation of Aloe Vera gel as prebiotics aimed at improving gastrointestinal health [6] . The effects of naturally occurring butyrate-producing probiotic Clostridium butyricum CGMCC0313.1 (CB0313.1) were examined by Shang H. group, in limiting the development of high fat diet (HFD)-induced obesity.…”
Section: Possible Prophylaxes Of Aloe Vera Gel Ingestion To Butyrate mentioning
confidence: 61%
“…Measurement of expired 13 CO2 after rectally administering [1][2][3][4][5][6][7][8][9][10][11][12][13] C]-butyrate in active and quiescent UC appears to be a promising and reliable method for evaluating disease activity and metabolic changes associated with amelioration of inflammation [10] . Gao Z. and his group examined the role of butyrate in the regulation of insulin sensitivity in dietary-obese C57BL/6J mice.…”
Section: Effect Of Butyrate To Insulin Resis-tance and Energy Expendimentioning
confidence: 99%
“…The ether extract from SCFAs fermentation medium of L. fermentum with AVJ revealed acetic, propionic and lactic acid as main SCFAs by GC/MSD analysis. In our earlier fermentation study [23,24] of Aloe vera gel with endophytic bacteria, Lactobacillus paralimentarium, Bacillus licheniformis, B. cereus and Clavispora lusitaniae in Aloe vera gel, only butyric acid was identified in in vitro fermented broth extract. The difference in SCFAs fermentation indicates the significant importance of probiotics comparing to prebiotics in present experiment.…”
Section: Resultsmentioning
confidence: 90%
“…The up-to-date descriptions of gut microbiota and role of SCFAs suggest that daily intake of the butyric acid fermentation extract from Aloe vera inner gel with endophytic bacteria, may provide the possible potential preventive and therapeutic roles in human health [25] . Intestinal microbiota producing butyrate might be developed for the therapeutic purpose to increase insulin sensitivity in humans with CR.…”
Section: Discussionmentioning
confidence: 99%